ANALISIS SIKAP PUBLIK TERHADAP ARTIS DAN KOMEDIAN YANG MEMASUKI RANAH POLITIK INDONESIA - Rinanda Gema Pangestika; Rendra Widyatama (Halu Oleo University, 2025)
The phenomenon of artists and comedians entering the political arena has become the focus of public attention. Many pro and con opinions as well as different perspectives from the public. Their involvement in politics often sparks debates regarding their credibility and competence as politicians. Therefore, this research aims to describe public attitudes towards artists and comedians entering the political arena and the factors influencing the public's decision to vote for them, considering that there has not been much previous research discussing public attitudes towards this issue in detail. The method used in this research is descriptive with a qualitative approach. Data collection techniques include in-depth interviews and secondary documentation. The research results indicate that the public holds three distinct views in response to the phenomenon: agree, disagree, and neutral. Public attitudes can be influenced by media consumption, the quality of political candidates, popularity and personal branding, as well as electoral institutions. Factors affecting the public's decision to vote for them include background, popularity, personal branding, capacity, quality, communication skills, and the unique characteristics possessed by artists and comedians.